What china is missing to be a market economy: China's political & economical models contradiction - Garcia, Mónica Maria Cristancho (2016)
China has been growing at a fastest pace than the rest of the world in the last two decades increasing the importance of its economy every day in the global field but sowing uncertainty and confusion among investors and the rest of the world due to the contradiction between its political and economic models. Economically, the People’s Republic of China has demonstrated to be more open to capitalism but its politics reveal a communist system in which there is no opportunity for a capitalist economy as it is originally conceived